Regulation and function of the melanization reaction in Drosophila. - Tang, H. (Fly, 2009)
The melanization reaction, involving the synthesis of melanin to encapsulate pathogens, is a prominent immune response in Drosophila, the mosquito and other insects and arthropods. Biochemical studies with large insects have defined a basic model for how melanization is activated and regulated upon microbial infection. In this model, recognition of a microorganism triggers a serine protease cascade that activates phenol oxidase (PO), a key enzyme in the melanin biosynthetic pathway, and serpin-type protease inhibitors are involved in inhibiting the cascade. In the past few years, genetic studies in Drosophila have identified serine proteases and serpins that regulate activation of PO and melanization in vivo. These studies, along with molecular genetic analysis of melanization in the mosquito, have provided new insight into the role that melanization plays in fighting microbial infection.